The Effects of Alcohol Drinking on Oral Microbiota in the Chinese Population - Liao, Ying; Tong, Xia-Ting; Jia, Yi-Jing; Liu, Qiao-Yun; Wu, Yan-Xia; Xue, Wen-Qiong; He, Yong-Qiao; Wang, Tong-Min; Zheng, Xiao-Hui; Zheng, Mei-Qi; Jia, Wei-Hua (International journal of environmental research and public health, 2022)
The dysbiosis of oral microbiota is linked to numerous diseases and is associated with personal lifestyles, such as alcohol drinking. However, there is inadequate data to study the effect of alcohol drinking on oral microbiota from the Chinese population. Here, we profiled the oral microbiota of 150 healthy subjects in the Chinese population by 16S rRNA gene sequencing. The results showed that drinkers had significantly higher alpha diversity than non-drinkers. A significant difference in overall microbiota composition was observed between non-drinkers and drinkers. Additionally, using DESeq analysis, we found genus Prevotella and Moryella, and species Prevotella melaninogenica and Prevotella tannerae were significantly enriched in drinkers; meanwhile, the genus Lautropia, Haemophilus and Porphyromonas, and species Haemophilus parainfluenzae were significantly depleted in drinkers. PICRUSt analysis showed that significantly different genera were mainly related to metabolism pathways. The oxygen-independent pathways, including galactose, fructose and mannose metabolism pathways, were enriched in drinkers and positively associated with genera enriched in drinkers; while the pyruvate metabolism pathway, an aerobic metabolism pathway, was decreased in drinkers and negatively associated with genera enriched in drinkers. Our results suggested that alcohol drinking may affect health by altering oral microbial composition and potentially affecting microbial functional pathways. These findings may have implications for better understanding the potential role those oral bacteria play in alcohol-related diseases.